Noty recenzyjne - CPH 33(2) (Czasopismo Prawno-Historyczne, 1981)
I. H. Crişan, Burebista and his time (S. R.) ... 180 Handbuch der europäischen Wirtschafts- und Sozialgeschichite, hrsg. von H. Kellenbenz, Bd. 2 — Mittelalter, hrsg. von J. A. van Houtte (S.R.) ... 180 Slova a dějiny, pod vedenim I. Němce (S. R.) ... 181 T. N. Bisson, Conservation of coinage. Monetary exploitation and its restreint in France, Catalonia and Aragon c.A.D. 1000-c. 1225 (S. R.) ... 182 The Comparative historical method in soviet mediaeval studies (S. R.) ... 182 A. S. Chorošev, Cerkov v social'no-političeskoj sisteme Novgorodskoj feodal'noj respubliki (S. R.) ... 183 Ju. G. Alekseev, Pskovskaj a Sudnaja Gramota i ejo vremja. Rozvitije feodal'nych otnošenij na Rusi XIV-XV vekov (S. R.) ... 183 Drevneišıe gosudarstva na teritorii SSSR, Materialy i issledovania, 1979 (G. Cz.) ... 184 G. Schlegel, Das Zisterzienserkloster Dargun 1172-1552 (J. W.) ... 184 Die geistlichen Ritterorden Europas. Hrsg. von J. Fleckenstein und M. Hellmann. Vorträge und Forschungen (H. O.) ... 185 S. Kuttner, The history of ideas and doctrines of canon law in the Middle Ages (W. U.) ... 186 S. Kuttner, Medieval Councils, decretals and collections of canon law. Selected essays (W. U.) ... 186 Diritto comune e diritti locali nella Storia dell'Europa. Atti del convegno di Varenna, 12-15 VI 1979 (W. U.) ... 187 T. Wyrwa, La pensée politique polonaise à l'époque de l'humanisme et de la renaissance (W. U.) ... 188 A. G. Man'kov, Ułoženie 1649 goda — kodeks feodal'nogo prawa Rossii (S. R.) ... 189 Parlamentarismus, hrsg. von K. Kluxen, wyd. 5 uzupełn. (S. R.) ... 189 Politiczeskije uczenija: istorija i sowremiennost. Marksizm i politiczeskaja myśl XIX wieka (H. O.) ... 190